Management of School-Community Partnership: Basis for Teacher Enhancement Program - Codilla, Leo, Jr. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to determine the practices and challenges in managing school-community partnerships in East Butuan District II elementary schools. The participants of the study were the Elementary School Teachers and School heads of East Butuan District II. Complete Enumeration is used in the study. The tested variables were practices of elementary schools, challenges in forging a school-community partnership, and the extent of school-community partnership. The findings reveal that the practices of elementary schools in the district showed a moderate level of manifestation except for participation in the athletic meet and preparation for the national achievement test (3.80), indicating a high level of manifestation. Similarly, the challenges forging school-community partnerships have moderate manifestation. On the other hand, the majority revealed either a moderate or low extent of school-community partnerships. This suggests that elementary schools in the East Butuan District II still want to manage school-community partnerships. It is interesting to note that practices and challenges significantly influence the extent of school-community partnership; a higher manifestation of practices but a lower manifestation of challenges implies a greater extent of school-community partnership.